Leptomeningeal Metastases - Abrey, Lauren E.; Chamberlain, Marc.; Engelhard, Herbert; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
Leptomeningeal Metastases provides the reader with an overview of the state-of-the-art therapy for the leptomeningeal patient with additional information on epidemiology, symptom management, new clinical trials, and current basic research in animal models for experimental therapies. "Leptomeningeal metastases remains a devastating manifestation of hematologic malignancies and solid tumors. Leading figures in the field review the pathophysiology and clinical consequences of this process. State-of-the-art treatment strategies are presented highlighting advances in current management." Steven T. Rosen, M.D. Series Editor.
Anatomy and Physiology of the Leptomeninges and CSF Space -- Leptomeningeal Neoplasia: Epidemiology, Clinical Presentation, CSF Analysis and Diagnostic Imaging -- Leptomeningeal Metastases from Solid Tumors (Meningeal Carcinomatosis) -- Leptomeningeal Metastases from Leukemias and Lymphomas -- Leptomeningeal Metastasis of Primary Central Nervous System (CNS) Neoplasms -- Leptomeningeal Cancer in the Pediatric Patient -- Neurosurgical Interventions for Leptomeningeal Tumor -- Current Treatment of Leptomeningeal Metastases: Systemic Chemotherapy, Intrathecal Chemotherapy and Symptom Management -- Radiation Therapy for Leptomeningeal Cancer -- Animal Models of Leptomeningeal Cancer -- Improving the Outcome of Patients with Leptomeningeal Cancer: New Clinical Trials and Experimental Therapies.
Keywords: Oncology .; Neurology .; Neurosurgery; Surgical oncology; Oncology; Neurology; Neurosurgery; Surgical Oncology